2020
DOI: 10.1002/jsfa.10947
|View full text |Cite
|
Sign up to set email alerts
|

Lipase nanogel catalyzed synthesis of vitamin E succinate in non‐aqueous phase

Abstract: BACKGROUND: In order to improve the stability of vitamin E and broaden its scope of application, an effective solution is to convert vitamin E into its derivatives. This work developed a new Candida rugosa lipase (CRL) nanogel based on modification of ionic liquid with vinyl functional groups. This novel CRL nanogel was used in the preparation process of vitamin E succinate based on the principle of non-aqueous enzymology. At the same time, various factors including enzyme concentration, substrate molar ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, for the products analyzed in this research, the 4 products showed transport potential through the first 3 tunnels located in CALB but with a greater possibility of exit through tunnel 2 (Figure 8) which were α-tocopherol acetate with E max −3.7 kcal/mol and E a 2 kcal/mol, α-ferulate tocopherol with E max −4.7 kcal/mol and E a 1.9 kcal/mol, and α-tocopherol nicotinate with E max −4.7 kcal/mol and E a 1.9 kcal/mol and through tunnel 3 was α-tocopherol succinate with E max −4.8 kcal/mol and E a 1.8 kcal/mol. It is important to note that although α-tocopherol acetate is the most commonly used ester in the pharmaceutical and cosmetic industry, α-tocopherol succinate, α-tocopherol nicotinate, and α-tocopherol ferulate are of fundamental importance for biological studies and biotransformation, as they are also addressed in the literature (Xin et al, 2011;Jiaojiao et al, 2021).…”
Section: Product Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the products analyzed in this research, the 4 products showed transport potential through the first 3 tunnels located in CALB but with a greater possibility of exit through tunnel 2 (Figure 8) which were α-tocopherol acetate with E max −3.7 kcal/mol and E a 2 kcal/mol, α-ferulate tocopherol with E max −4.7 kcal/mol and E a 1.9 kcal/mol, and α-tocopherol nicotinate with E max −4.7 kcal/mol and E a 1.9 kcal/mol and through tunnel 3 was α-tocopherol succinate with E max −4.8 kcal/mol and E a 1.8 kcal/mol. It is important to note that although α-tocopherol acetate is the most commonly used ester in the pharmaceutical and cosmetic industry, α-tocopherol succinate, α-tocopherol nicotinate, and α-tocopherol ferulate are of fundamental importance for biological studies and biotransformation, as they are also addressed in the literature (Xin et al, 2011;Jiaojiao et al, 2021).…”
Section: Product Transportmentioning
confidence: 99%
“…In 2011, Chunhua et al (2011) also synthesized enzymatically, using Candida antarctica lipase B (Novozym 435), to obtain tocopherol succinate, modifying the biocatalyst to improve its catalytic performance using acetic anhydride, propionic anhydride, and succinic anhydride separately, and with the best modifying agent succinic anhydride (1: 5) yielded 94.4%. Jiaojiao et al (2021) used a nanogel-modified Candida rugosa lipase to obtain vitamin E succinate and obtained a yield of approximately 62% with a reaction time of 15 h. Xin et al (2011), on the other hand, verified the ability of lipases to catalyze through the transesterification reaction of α-tocopherol and ethyl ferulate to obtain tocopherol ferulate, and it can be observed that only Candida antarctica lipase B and Candida rugosa lipase catalyzed the transesterification reaction. A yield of 25.2% tocopherol ferulate was obtained using a 5:1 molar ratio of α-tocopherol to solvent-free ethyl ferulate in 72 h of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse immobilization approaches, in situ polymerization in the presence of enzymes has been developed as a reliable approach, which creates typically enzyme-loaded nanogels with regulated size and properties. , To do so, monomers need to be introduced on the surface of an enzyme via either chemical binding or physical interaction, followed by the copolymerization with a cross-linker . For example, acryloyl groups have been attached covalently to lysine residues of diverse enzymes such as lipase, horseradish peroxidase, urate oxidase, carbonic anhydrase, catalase, and glucose oxidase . The subsequent polymerization of acrylamide monomers creates a variety of enzyme nanogels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with the higher requirements for green chemistry processes in recent years, the synthesis of VES by toxic chemical methods such as triethylamine 7 and 4-dimethylaminepyridine 8 was gradually replaced by green and efficient enzymatic synthesis. 9 Because vitamin E and succinic anhydride are prone to acylation, based on what we know about industrial production, we consider that the yield of VES in industrial production is at least more than 95%. Our previous studies suggested that the yield of VES can only reach 46.95% via the catalytic activity of natural lipase.…”
Section: Introductionmentioning
confidence: 99%